Pendidikan Kewarganegaraan dan Pembentukan Karakter: Membentuk Individu yang Bertanggung Jawab dan Peduli - Yudha, Willy Fadhilah Wira; Hudi, Ilham; Marisa, Vania; Farliando, Ridho Arya; Putri, Yolanda Ardila; Avicenna, Achyar Zein; Admi, Nurhayati Marjuni (International Forum of Researchers and Lecturers, 2024)
Citizenship education is an important component in character formation that can improve the moral quality of the Indonesian nation. Citizenship education can be an effort to create character or morals based on Pancasila regarding the understanding, values , and behavior of the nation's generation. In character formation, citizenship education is the main effort to improve skills in terms of critical thinking, collaborative communication skills, and good decision-making skills. Citizenship education focuses onl forming a quality young generationlby optimizing the potential in each individual which is reflected in awareness, understanding, and behavior. With Citizenship Education, it is hopedl that it can be an effort to strengthen the identity and quality of the nation by creating individuals whol are not only intellectually intelligent but also have strong, responsive, critical, creative, responsible character and can contribute positively to societyl andl the nation.